Association of Antibiotic and Heavy Metal Resistant Bacteria Screened from Wastewater - Gautam, Bikram; Adhikari, Rameshwar (International Journal of Environment, 2018)
Wastewater treatment plant is a potential reservoir contributing to the evolution and spread of heavy metal and antibiotic resistant bacteria. The pollutants such as biocides, antibiotics, heavy metals are to be feared for as they have been known to evoke resistance in microorganisms in such polluted environment. The aim of this study was to the isolate bacteria from the treated wastewater and assess the resistance pattern of the isolates against antibiotics and heavy metals. Grab sampling was performed from April to June 2017, from the treated effluent from the secondary treatment plant. To assess the resistance pattern for antibiotic(s) and heavy metal(s), antibiotic susceptibility test and minimum inhibitory concentration by cup well method were performed respectively. Staphylococcus aureus, Enterococcus faecalis, Citrobacter freundii, Escherichia coli, Enterobacter aerogenes, Proteus mirabilis, P. vulgaris, Salmonella Typhi, Pseudomonas aeruginosa were isolated. Multi drug and heavy metal resistant isolates were screened. Fisher’s exact test revealed that there is a significant association (p< 0.001) between antibiotic resistance pattern and resistance patterns at dilution of 2500 g/L (25%). Cramer’s V test revealed that the effect size of antibiotic resistance pattern and heavy metal resistance pattern at dilution 2500 g/L is medium. P. aeruginosa was able to resist the metal concentration up to 10000 g/L (100%) dilution of Fe++. Heavy metal resistant bacteria can be safely used to lower chemical concentration in the environment once their harmful genes are edited, knocked etc. so that risks of evoking antibiotic resistance could be minimized.